2010
DOI: 10.1177/1744259110382229
|View full text |Cite
|
Sign up to set email alerts
|

Hot box investigations and theoretical assessments of miscellaneous vacuum insulation panel configurations in building envelopes

Abstract: Vacuum insulation panels (VIPs) are regarded as one of the most promising existing high performance thermal insulation solutions on the market today as their thermal performance typically range 5 to 10 times better than traditional insulation materials. However, the VIPs have several disadvantages such as risk of puncturing by penetration of nails and that they cannot be cut or fitted at the construction site. Furthermore, thermal bridging due to the panel envelope and loadbearing elements may have a large eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…PCM by itself is not an insulation material in principle but may still be an important part of the thermal building envelope. At our lab, both theoretical [2][3][4][5][6][7] and experimental work [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] were conducted alongside to derive new materials that go beyond these state-of-the art materials, thus dawning the birth of the concepts such as nano insulation materials (NIM) through the utilization of the Knudsen effect [24][25][26][27][28][29][30], where experimental investigations so far have concentrated about making hollow silica nanospheres (HSNS) [30][31][32][33][34][35][36][37][38], thus enabling thermal insulation and improved energy efficiency from a 'nano' perspective.…”
Section: Introductionmentioning
confidence: 99%
“…PCM by itself is not an insulation material in principle but may still be an important part of the thermal building envelope. At our lab, both theoretical [2][3][4][5][6][7] and experimental work [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] were conducted alongside to derive new materials that go beyond these state-of-the art materials, thus dawning the birth of the concepts such as nano insulation materials (NIM) through the utilization of the Knudsen effect [24][25][26][27][28][29][30], where experimental investigations so far have concentrated about making hollow silica nanospheres (HSNS) [30][31][32][33][34][35][36][37][38], thus enabling thermal insulation and improved energy efficiency from a 'nano' perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The low temperatures in the simulations may be caused by the application of the VIP upper limit declared thermal conductivity of 0.005 W/(mK) (Porextherm, 2009), as the real thermal conductivity may be as low as 0.004 W/(mK) (Binz et al, 2005). Measurements have shown that both the conductivity and the thickness of different VIPs may vary, e.g., Grynning et al (2010) measured conductivities somewhat higher than the declared ones and panel thicknesses that were less than stated.…”
Section: Comparison Of Measured and Simulated Resultsmentioning
confidence: 94%
“…Therefore, the literature review shows that the calibrated hot box is the most used [3,4,6,13,17,19,20,[23][24][25][26]28,30,32,33,36,37] followed by the guarded hot box [5,7,14,15,18,21,22,29,31,34,35] and the simple hot box [16,27,38]. The measuring systems always employ analog probes and the thermocouples are more widely used [3][4][5][6][13][14][15][16]18,[21][22][23][24][25][26][27]29,31,[33][34]…”
Section: Common Systems and Literature Backgroundmentioning
confidence: 99%